Amino acid-assisted controlling the shapes of rutile, brookite for enhanced photocatalytic CO2 reduction. Issue 31 (19th July 2017) - Truong, Quang Duc; Le, Thi Hang; Hoa, Huu Thu
Abstract : Rutile and brookite titania with tunable shape have been synthesized. The investigation results show that the photcatalytic CO2 reduction activity of rutile increases with increasing percentage of {111} surface and brookite with exposed {210} facets exhibit a notable photocatalytic reduction of CO2 to methanol. Abstract : TiO2 nanoparticles with a controlled crystalline phase, size, shape and surface structure have been synthesized by a facile hydrothermal method using a water-soluble titanium complex and amino acid as the structure-directing and shape-controlling agents. The titania phases of rutile or brookite can be easily tuned by using different amino acid additives. Rutile nanorods with a high aspect ratio have been obtained in the presence of glutamic acid. Small nano-sized and well-faceted brookite can be synthesized using lysine as a pH-adjusting and shape-controlling agent. Amino acids play crucial roles in determining the crystalline phase as well as size and shape of the synthesized nanoparticles. The synthesized TiO2 rutile and brookite with different shapes have been evaluated for photocatalytic activity by means of the reduction of carbon dioxide to methanol. The investigation results reveal that the methanol yield on rutile and brookite strongly depends on the crystalline phase, size, shape and surface structure of the synthesized nanocrystals. Among the rutile nanocrystals, the photocatalytic activity increases with an increasing percentage of the {111} surface. Brookite with exposed {210} facets exhibits a notable photocatalytic activity for CO2 reduction presumably due to its specific surface structure with a spatial separation of reductive and oxidative sites. Our studies demonstrate the abilities of shape-control and facet-selectivity in determining photocatalytic activity, representing a critical step forward in the designing of high performance nanostructures for the reduction of CO2 .